ANALYSIS FACTOR OF MARKETING STRATEGY OF FUNDING DECISION OF CUSTOMERS CHOOSE BAITUL MAL WAT TAMWIL (BMT) IN KOLAKA REGENCY, INDONESIA - Muhammad Zakariah; Muhammad Askari Zakariah; Dwi Puji Astuti; Ridwan Ridwan; Sri Maryam (Jurnal Ekonomi Bisnis Syariah, 2018)
were carried out, covering Validity and reliabilita, then continued with, test multiple regression analysis using SPSS version 16.0. The results showed Community decision base on calculated rated R square of 0.975 or 95.7% strongly influenced by the factor have been determined, such as product, price, place, and promotion. The value of the constant is 0.026, 0.925 for products, 0.889 for price, 0.654 for place, 1.554 for promotion. then it can be concluded from these data regression equation is: Y = 0.026 + 0.925X1 + 0.889X2 + 0.654X3 + 1.554X4. Concluded that factor marketing strategy of funding decision of customer choose BMT in Kolaka Regency is product, place, and promotion. However, variable price was not significantly.